Thermal performance of waste materials as aggregate replacement in asphalt pavement - Aletba, Salam Ridha Oleiwi; Norhidayah, Abdul Hassan; Eeydzah, Aminudin; Putra Jaya, Ramadhansyah; Nurul Athma, Mohd Shukry; Nordiana, Mashros; A. Aziz, Md Maniruzzaman; Md. Nor, Hasanan (IOP Publishing, 2019)
The high surface temperature of the conventional asphalt pavement due to high solar energy absorption could contribute to the Urban Heat Island (UHI) phenomenon. Concurrent with this phenomenon, rapid urbanization and industrial development have led to a large quantity of waste products available for disposal or recycling. Therefore, this study investigates the thermal performance of selected waste materials that could potentially be used as aggregate in asphalt pavement to combat the problem of increased pavement surface temperature. A number of waste materials were selected for the thermal performance measurement and compared to granite as conventional aggregate. The cylindrical and slab samples of AC14 dense graded asphalt were prepared for the different selected aggregate types. The samples were then measured for solar reflectance using Spectroradiometer. In addition, the surface and internal temperature profiles of the samples were monitored using infrared camera and thermocouples, respectively, in exposed environments. Based on the results, it is possible to use some of the waste materials as an aggregate replacement in order to reduce the UHI impact.